Morpho-physiological responses of Malakatmon (Dillenia luzoniensis Merr.) to different organic amendments in laterite soil - Pascua, Julius G.; Quimado, Marilyn O.; Maldia, Lerma SJ.; Tinio, Crusty E.; Reyes Jr., Tomas D.; Combalicer, Marilyn S. (Brawijaya University, 2026)
Mining in the Philippines has caused extensive land degradation, underscoring the need for resilient native species in ecological restoration. This study investigated the morpho-physiological responses of Malakatmon (Dillenia luzoniensis), a vulnerable native tree, to nickel-rich laterite soils amended with biochar, cow manure, or vermicompost. Conducted under nursery conditions at the University of the Philippines, Los Baños, the research evaluated seed germination in garden and laterite soils and assessed seedling growth under 2%, 4%, and 6% organic amendment rates. Germination rates were comparable between garden (78.33%) and laterite soils (72.33%), and a strong positive correlation was observed between germination rate and energy (r = 0.86). Seedling mortality reached 16.67% in unamended laterite but declined significantly with cow manure (2.22%) and vermicompost (10.00%). In contrast, biochar, particularly at 6%, increased mortality to 63.33%. Organic amendments, especially cow manure and vermicompost, enhanced seedling performance. Treated plants showed greater leaf number (6.10 and 5.90), leaf area (1.00 cm² and 1.13 cm²), root number (14.87 and 10.95), root length (9.64 cm and 9.25 cm), and chlorophyll content (33.05 and 32.59 µmol cm?²) compared to controls. Higher biochar concentrations, however, inhibited root development. Moderate correlations were found between root and leaf traits (r = 0.54; r = 0.48), while stomatal traits remained stable. Overall, D. luzoniensis demonstrates strong potential for rehabilitating mined lands, with cow manure and vermicompost proving effective in promoting early seedling establishment and growth.